Food Waste: Kontraproduktif dan Potret Kemiskinan, Stunting, dan Kerawanan Pangan di Provinsi Riau - Yusnatida Eka Nizmi; Herry Wahyudi; Hasan Warso Syahputra; Ahmad Ibrahim Roni Surya Hasibuan; Rahmi Yulia; Tuah Kalti Takwa (Universitas Pendidikan Ganesha, 2024)
Riau Province faces three social problems: poverty, stunting, and food insecurity. The public understands food waste as a threat to food security. Suppose the continuous food waste issue needs to be addressed. In that case, it will directly impact sustainable food availability due to the massive amount of wasted food that is still fit to eat and nutritionally adequate. This research aims to elaborate on the counter productiveness of food waste with a portrait of poverty, stunting, and food insecurity in Riau Province, which are interconnected. Qualitative methods are used in this research, with the data collection techniques used being interviews, questionnaires, and literature analysis. The findings reveal that food waste behavior contradicts Riau Province's efforts to address its main problems. Collaboration with related agencies is essential to raise awareness and combat food waste, ensuring it does not hinder the fight against poverty, stunting, and food insecurity in Riau Province.